Kajian Yuridis Perkawinan Adat Cako pada Masyarakat Hukum Adat Desa Cumbi Kabupaten Manggarai Ditinjau dari Undang-Undang Nomor 1 Tahun 1974 tentang Perkawinan - Yohanes Patrick; Sukardan Aloysius; Orpa Juliana Nubatonis (LPPM Universitas Sains dan Teknologi Komputer, 2024)
The aim of this research is to determine the factors that drive the people in Cumbi Village, Manggarai Regency, to perform Cako customary marriages, to understand the process of Cako customary marriage in the traditional community of Cumbi Village, and to ascertain the validity of Cako customary marriages in the customary law of Cumbi Village, Manggarai Regency, in accordance with Law Number 1 of 1974 concerning Marriage. This study is an empirical legal research using an approach involving interviews as primary data sources and literature reviews, including books, regulations, and other scholarly writings related to the research. The conclusions of this study include, among others: Firstly, Cako customary marriages conducted in Cumbi Village are motivated by several factors, such as strengthening family ties, arranged by parents, preventing inheritance from shifting or dividing along other bloodlines, proximity of residence, lighter financial burden (belis), and preserving the Manggarai culture, as Cako customary marriages are part of Manggarai culture. Secondly, the procedure for Cako customary marriage in Cumbi Village begins with the Kamba Lembor Cako ceremony. The Cako marriage procedure is then followed by the courtship or weda rewa tuke mbaru stage. Subsequently, the event continues with the implementation of the marriage or cikat kina waga kaba. The last procedure is the escorting of the bride to the groom's house. Thirdly, Cako customary marriages in Cumbi Village can still be conducted in accordance with the customary law of Cumbi Village as long as they do not contradict positive law. Additionally, the Catholic Church, by providing dispensations for couples with blood relationship hindrances, can be a way for Cako customary marriages to be legally valid both religiously and according to positive legal regulations.